The riot as harbinger of crisis: On the excesses during the G20 summit 2017 in Hamburg - Uhlmann, Sarah (Momentum Quarterly, 2018)
During the G20 Summit in Hamburg we have seen immense riots, which led to numerous discussions in the press. In these, the delinquency of the rioters was often in the foreground. A more far-reaching political or scientific interpretation of the events was clearly missing. This deficit is also a result of the fact that social movement and protest studies hardly offer any research approaches for the analysis of riots. The present article understands riots as a social phenomenon and therefore strives for a deeper understanding by shedding light on ideological and psychosocial as well as socio-structural causes. The riots will be interpreted as a crisis phenomenon with the help of political-economic works like those by Joshua Clover, but the eruption itself can only be understood from a relational perspective. The scale of the riots in Hamburg was only possible because the heterogeneous protest groups formed a coalition in view of their shared opposition to the police, in which the usual boundaries between the different political spectra but also social strata were briefly overturned, thus creating a mass of protestors that was difficult to control.